Ograniczenie autonomii jednostki, a może ochrona konstytucyjnych praw i wolności człowieka? Normatywne aspekty stosowania „przymusu bezpośredniego” w psychiatrii - Lisowska, Anna (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
The publication is concentrated on the use of direct coercion in psychiatry. I tried to answer on the question whether using direct coercion always leads to the limitation of individual autonomy, whether provides the protection of constitutional law and human freedom. Unraveling above background would be impossible without refer to the human rights which is a source of basic laws and freedom. The reference to limitation of individual autonomy was based on Bioethical Convention. Situation and requirements became closer which explain and can create a foundation for using a direct coercion. In this article, circumstances were intorduced in which in compliance with law, using direct coercion is acceptable as well as rules and the course. The relationship was noticed between its application and required agreement of individual to grand the health care.